Effects of the number of ball touches among elite youth players during small-sided soccer games - Mahlangu, P; Kubayi, A; Toriola, A; Monyeki, A. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: This study investigates the effects of manipulating the number of ball touches (free play vs. two touches) on the physical and technical actions of elite male youth soccer players during 5v5 + 2 goalkeepers (GKs) small-sided games (SSGs).